Formación de maices mejorados de alto valor nutritivo y adaptados a las diversas zonas agrícolas del país. - Harpstead, D.D.; Cassalett D., C.; Rivera, J. A.; Sarria V., D.; Rubio, A. M.; Arboleda R., F.; Sánchez M., R.; Díaz A., C.; Diaz B., E.; Ramírez E., R.; Ramírez Guzmán, M.C.; Rivera Gómez, J.A.; et al. (Instituto Colombiano Agropecuario, 2018)
Maíz-Zea mays